Outcome of probing and syringing in congenital nasolacrimal duct obstruction at various age groups in a tertiary eye center in Western Nepal - Shrestha, Koshal; Bhattarai, Binita; Manandhar, Laxmi Devi; Rai, Salma KC; Pandey, Arniko; Gurung, Shanti (Asian Journal of Medical Sciences, 2018)
Background: Congenital nasolacrimal duct obstruction (CNLDO) is one of the commonest problems encountered in daily ophthalmology practice. Though probing and syringing is the mainstay of management of CNLDO, there is no clear guideline about the optimal time to perform. Aims and Objective: To evaluate the efficacy of probing and syringing in cases of congenital nasolacrimal duct obstruction in various age groups. Materials and Methods: In this prospective, hospital based, interventional, cross-sectional study done over a period of 2 years (July 2015- June 2017), children of various age ranging from 10 days to 8 years who underwent probing and syringing under general anesthesia for CNLDO refractory to conservative measures were included. Results: Children of as young as 10 days to as older as 8 years underwent probing and syringing with male to female ratio of 1.2:1. Overall success was 80.6% (58/72) which was statistically significant when analyzed with age (P = 0.006). Majority of cases with successful outcome were below 24 months of age (90.62%). There was predominance of membranous obstruction (128/194) over bony obstruction (66/194). Conclusions: Nasolacrimal duct probing under GA is a safe and viable option as a primary treatment modality for CNLDO. Though the success of probing is high in the younger children, it’s worthwhile to consider the same in older children at least up to 5 years of age before going for more invasive procedure like DCR surgery since more than 2 third of probing has successful outcome up to that age. Asian Journal of Medical Sciences Vol.9(6) 2018 57-61